2019
DOI: 10.1021/acsami.9b13840
|View full text |Cite
|
Sign up to set email alerts
|

Symmetry-Breaking Actuation Mechanism for Soft Robotics and Active Metamaterials

Abstract: Magnetic-responsive composites that consist of soft matrix embedded with hard-magnetic particles have recently been demonstrated as robust soft active materials for fast-transforming actuation. However, the deformation of the functional components commonly attains only a single actuation mode under external stimuli, which limits their capability of achieving tunable properties.To greatly enhance the versatility of soft active materials, we exploit a new class of programmable magnetic-responsive composites inco… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
90
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 156 publications
(91 citation statements)
references
References 55 publications
1
90
0
Order By: Relevance
“…Figure illustrates the working principle of these unit cells. They are constructed using the concept of the magnetic‐responsive asymmetric joint design, [ 13a ] in which two oppositely polarized hmSAM beams are connected side‐by‐side with a small gap placed between them. When a downward magnetic field (negative B ) is applied, the hmSAMs tend to rotate in the opposite directions, closing the gap between them and causing a bending deformation of the joint, referred to as the bending mode (Figure 1a, left).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Figure illustrates the working principle of these unit cells. They are constructed using the concept of the magnetic‐responsive asymmetric joint design, [ 13a ] in which two oppositely polarized hmSAM beams are connected side‐by‐side with a small gap placed between them. When a downward magnetic field (negative B ) is applied, the hmSAMs tend to rotate in the opposite directions, closing the gap between them and causing a bending deformation of the joint, referred to as the bending mode (Figure 1a, left).…”
Section: Resultsmentioning
confidence: 99%
“…The architecture of this new metamaterial employs an asymmetric joint design using hmSAMs that allows rapid transition between two distinct actuation modes (bending and folding) under opposite‐direction magnetic fields. [ 13a ] The subsequent application of mechanical forces leads the metamaterial architecture to transform into two distinct shapes, a process referred to as deformation mode branching, which is otherwise unobtainable using either stimulus independently. The deformation mode branching also leads to dramatically different physical behaviors and allows the new metamaterial to have a much broader range of tunability in properties such as mechanical stiffness and acoustic bandgaps.…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have also shown techniques to exploit combinations of bending and folding in magnetically‐actuated, square metamaterial unit cells that exhibited as much as 200% stiffness change under application of magnetic field. [ 208 ] Tuning of internal resonances is studied in ref. [ 209 ] to manipulate wave propagation in a metamaterial frame consisting of a lattice structure and a pair of embedded electromagnets for each unit cell.…”
Section: Active Mechanical Metamaterialsmentioning
confidence: 99%
“…[130] The authors found that this increased freedom of the tail was possible by discretizing magnetically susceptible parts in the elastic tail instead of making a continuum. The widespread availability of multimaterial 3D printing and origami/kirigami technologies at the time, indeed, boosted creativity to realize more complex structures with discretized magnetic parts, such as frog-like swimmers by Zhao and coworkers, [99] starfish-like simmers by Nuzzo and coworkers, [90] and jellyfish-like swimmers by Sitti and coworkers (Figure 3c) [131] and Huang and coworkers. [132] There are a few other recent magnetic swimmer studies that deserve special mention.…”
Section: Magnetic Swimmersmentioning
confidence: 99%